Effects of high-intensity exercise on rehabilitation of patients after stroke: a systematic review and meta-analysis of randomized controlled trials with high quality - Li, Shuang; Dou, Yuchang; Li, Hong (Frontiers in Neurology, 2025)
ObjectivesTo present the latest systematic review and meta-analysis of high-quality randomized controlled trials (RCTs) comparing high-intensity exercise with routine rehabilitation in stroke patients.MethodsPubMed, Web of Science, and Cochrane were used to searching literature up to October 2024. RCTs with sample size of ≥50 individuals were included. Primary outcomes assessed were the Six-Minute Walking Test (6MWT), Ten-Meter Walk Test (10MWT), VO2peak, Berg Balance Scale (BBS), Timed Up and Go test (TUG), and Montreal Cognitive Assessment (MoCA). Standardized mean differences (SMD) with 95% confidence intervals (CI) were used for pooling data. Stability was evaluated by sensitivity analysis.ResultsSeven RCTs with 724 participants were included. Meta-analysis revealed significant improvements in the 6MWT (SMD: 0.28; 95% CI: 0.11, 0.45) and BBS (SMD: 0.35; 95% CI: 0.03, 0.67) in the high-intensity exercise group. However, high-intensity exercise had no significant effect on VO2peak, TUG, or 10MWT. Sensitivity analysis showed that all outcomes were stable except for the 10MWT. No significant publication bias was detected for any indicator.ConclusionHigh-intensity exercise significantly improves 6MWT and BBS in stroke patients, but does not significantly affect TUG, VO2peak, 10MWT, or MoCA. Clinicians should encourage stroke patients with walking function to engage in structured high-intensity exercise to improve cardiopulmonary function.Systematic review registrationCRD42024623036 Publicly accessible URL: https://www.crd.york.ac.uk/PROSPERO/view/CRD42024623036.